Comparison of chemical treatment methods for loblolly pine to utilize as enzyme hydrolyzate feedstock. (November 2016) - Jain, Arpan; Bridges, William C.
Abstract: The ground pine wood chips (GPWC) were examined through chemical treatment methods employing alkaline hydrogen peroxide treatment (AHP, consisted of 50 g L −1 potassium hydroxide, and 50 g L −1 hydrogen peroxide with added water at 78 °C for 24 h), and ethyl-hydro-oxides treatment (EHOs, consisted of 60% ethanol (of total solution), 50 g L −1 potassium hydroxide, and 50 g L −1 hydrogen peroxide with added water at 78 °C for 24 h). The effects of chemical treatments on GPWC were examined through combination of chemical composition followed by enzymatic hydrolysis (using Accellerase ® 1500). The application of EHOs treatment removes the foaming issue that currently occurs due to AHP treatment at the elevated temperature. A removal of the foaming phenomenon increased the enzymatic glucan conversion (>70%) which is important in increasing the efficiency of biorefinery. The interaction of different variables in EHOs solvent formulations including ethanol concentration (0–60%), potassium hydroxide concentration (0–50 g L −1 ), hydrogen peroxide concentration (0–50 g L −1 ), and processing temperature (38 °-78 °C) were analyzed through four variables response surface methodology using glucan conversion and total polysaccharide conversion as responses. The glucan conversion and total polysaccharide conversion were analyzed to determine the specific and overall effects of Accellerase ® 1500 on the amorphous polysaccharide contents of GPWC resulted through EHOs treatment formulations, respectively. The implications of all these findings are discussed with the available literature. Highlights: Analysis of solvent polarities of chemical treatments for pine wood conversion. Chemical and biological analyses of chemically treated pine wood chips. Four variables response surface methodology for process optimization. Importance of foam controlling in a scale-up chemical treatment process.